2007
DOI: 10.1002/jnr.21508
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor‐κB decoy amelioration of spinal cord injury‐induced inflammation and behavior outcomes

Abstract: Spinal cord injury (SCI) results in a pathophysiology characterized by multiple locomotor and sensory deficits, resulting in altered nociception and hyperalgesia. SCI triggers an early and prolonged inflammatory response, with increased interleukin-1beta levels. Transient changes are observed in subunit populations of the transcription factor nuclear factor-kappaB (NF-kappaB). There were decreases in neuronal c-Rel levels and inverse increases in p65 and p50 levels. There were no changes in neuronal p52 or Rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 57 publications
4
39
1
Order By: Relevance
“…Secondary phase increases the pathology of SCI because of the activation of inflammatory responses [4][5][6]. The expression of NF-kB and other transcription factors like cRel, Rel B, Rel A/p65, p50 and p52 are increased as a result of the activation of inflammatory responses, however, preventing activation of NF-kB can attenuate secondary damage after SCI [7][8][9][10]. It has been shown in different reports that a direct inhibition of I-kB kinase (IKK) can result in regulation of inhibition of products of NF-kB genes [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Secondary phase increases the pathology of SCI because of the activation of inflammatory responses [4][5][6]. The expression of NF-kB and other transcription factors like cRel, Rel B, Rel A/p65, p50 and p52 are increased as a result of the activation of inflammatory responses, however, preventing activation of NF-kB can attenuate secondary damage after SCI [7][8][9][10]. It has been shown in different reports that a direct inhibition of I-kB kinase (IKK) can result in regulation of inhibition of products of NF-kB genes [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, CAPE may directly inhibit transcriptional activity of NF-κB irrespective of down-regulation of IL-1β gene expression, because it has been reported that CAPE prevents the binding of NF-κB to DNA (20). In fact, an NF-κB decoy ameliorates behavior outcomes in SCI animal models (25), supporting the involvement of NF-κB in the CAPE-dependent amelioration of locomotor function.…”
Section: Cape Attenuates the Expression Of Inflammation-inducible Genmentioning
confidence: 95%
“…The nuclear factor (NF)-κB transcription factor is a key mediator in inflammatory responses and has been implicated in the progression of this secondary injury. NF-κB can be activated by a variety of stimuli, including inflammatory cytokines such as interleukin (IL)-1, which is released from spinal cord-resident cells and/or infiltrating monocytes (4,25). In response to SCI, NF-κB induces the transcriptional activation of proinflammatory genes including inducible nitric oxide (NO) synthase (iNOS), which produces NO, and cyclooxygenase-2 (COX-2) (23).…”
mentioning
confidence: 99%
“…Different genes are expressed that mediate inflammatory responses by transcribing a family of transcription factors include p52, p50, RelB, RelA/p65 and cRel [7,8]. Inhibition of the NF-kB pathway works as a treatment for SCI due to inhibition of various gene products that are mediated through the NF-kB pathway [9,10].…”
Section: Introductionmentioning
confidence: 99%